Molecular Dynamics Simulations on Gas-Phase Proteins with Mobile Protons: Inclusion of All-Atom Charge Solvation - Konermann, Lars (The journal of physical chemistry. B, 2017)
Molecular dynamics (MD) simulations have become a key tool for examining the properties of electrosprayed protein ions. Traditional force fields employ static charges on titratable sites, whereas in reality, protons are highly mobile in gas-phase proteins. Earlier studies tackled this problem by adjusting charge patterns during MD runs. Within those algorithms, proton redistribution was subject to energy minimization, taking into account electrostatic and proton affinity contributions. However, those earlier approaches described (de)protonated moieties as point charges, neglecting charge solvation, which is highly prevalent in the gas phase. Here, we describe a mobile proton algorithm that considers the electrostatic contributions from all atoms, such that charge solvation is explicitly included. MD runs were broken down into 50 ps fixed-charge segments. After each segment, the electrostatics was reanalyzed and protons were redistributed. Challenges associated with computational cost were overcome by devising a streamlined method for electrostatic calculations. Avidin (a 504-residue protein complex) maintained a nativelike fold over 200 ns. Proton transfer and side chain rearrangements produced extensive salt bridge networks at the protein surface. The mobile proton technique introduced here should pave the way toward future studies on protein folding, unfolding, collapse, and subunit dissociation in the gas phase.